Integrating Halal Consumer Awareness and Sustainability to Enhance Satisfaction and Purchase Decisions in the Franchise Ice Cream Market - Naya Yasinta Ramadhanti; Masagus Haidir Tamimi (Journal of Applied Food Technology, 2025)
Halal products contribute to sustainability by promoting ethical sourcing, transparency, and responsible production practices. This study explores how halal consumer awareness, which includes halal certification, halal consciousness, and ingredient information, influences satisfaction and purchase decisions in franchise-based ice cream outlets in Bandung, Indonesia. Data were collected from 130 respondents through a structured survey and analyzed using Structural Equation Modeling (SEM). The results show that halal awareness positively affects both satisfaction and purchasing behavior, with satisfaction serving as a mediating factor between awareness and purchase decisions. Halal certification and ingredient transparency are identified as the strongest indicators shaping awareness, while product taste and service quality are key drivers of satisfaction. The findings emphasize that understanding halal principles and maintaining product transparency enhance consumer trust, loyalty, and long-term engagement. The study underscores the role of halal assurance as part of a broader sustainability strategy, providing insights for developing responsible and competitive halal food marketing practices.